Migration, Education, and Adaptation: The Effects of Forced Displacement on Students After Disasters - Engin Güneş; Gürkan Sarıdaş (Journal of Research in Social Sciences and Language)
This study analyzes the socio-economic, psychological, and academic adaptation processes of individuals who were forced to migrate following the Kahramanmaraş earthquakes on February 6, 2023. In this study, a mixed design combining qualitative and quantitative research methods was selected. Descriptive content analysis and statistical analysis techniques were used as the research design. The findings indicate a decline in students' academic performance, an increased risk of social exclusion, and a lack of psychological resilience. The study emphasizes the need to develop educational policies and strengthen social work mechanisms for students who migrate after disasters. provided.